Analisis Modal Usaha, Laba Usaha Dan Jam Kerja Di Apotek Syifa Medika Kota Sukabumi - Damayanti, Maya; Suherman, Acep (Universitas Dian Nuswantoro, 2023)
This study aims to find out how to analyze working capital, operating profit and working hours at Syifa Medika Pharmacy. To obtain in-depth and accurate results, this research focused on Syifa Medika Pharmacy located in the city of Sukabumi. This research uses a descriptive method with a qualitative approach. The author conducts data collection through interviews, documentation and observation. Data management by means of descriptive analysis is a technical writing by presenting all data obtained through interviews, documentation and library materials and analyzing them with written source guidelines. From the results of the study, the author analyzed working capital, operating profit and working hours It plays an important role in running a business, which means that every increase in capital, operating profit obtained and additional hours of working hours will increase the profit of Syifa Medika Pharmacy.